Small cell lung carcinoma presenting with acute disseminated encephalomyelitis - Summerfield, R (The British Institute of Radiology., 2010)
Acute disseminated encephalomyelitis (ADEM) is a demyelinating disease characterised by subcortical high-signal white matter lesions on T(2) weighted MRI. It most commonly occurs in children following an acute viral illness. We present a case study in which ADEM was the presenting condition in an adult female with small cell lung carcinoma. We discuss the evidence in the literature suggesting that ADEM may be viewed as a paraneoplastic syndrome.